Հարավային Հայաստանի առնչությունները Հյուսիսային Սիրիայի հետ Ք. ա. 3-2–րդ հազարամյակների սահմանին - Բոբոխյան, Արսեն («Զանգակ - 97»)
The southem regions of Armenian Highland (respect. the provinces of Tsopk, Aldznik, Korduk of historical Armenia) have had permanent contacls with North Syria (as well as North Mesopotamia), in particular periods forming even cultural zones with the above mentioned territories. The aim of the article is to show that in the period under consideration the southern Armenian regions had active contacts with North Syria, but they had mcre trade significance. Moreover, the main road of communications is supposed to be the Euphrales route through Tsopk, meanwhile the regions of Aldznik and Korduk were the main artery for the relations with North Mesopotamia.
Keywords: Պատմություն; Քաղաքականություն